COMMON RISK FACTORS IN PATIENTS WITH INTRAUTERINE FETAL DEATH - Malik, Rukhsana; Khan, Nadia Rashid; Arif, Aisha; Ayoub, Saima; Perveen, Saima (Journal of Postgraduate Medical Institute, 2016)
Objective: To find out common risk factors in patients with intra-uterine fetal death. Methodology: This descriptive cross sectional study was carried out on 155 patients. Study was conducted at Department of Gynecology Lady Reading Hospital Peshawar from 30th August 2010 to 28th February 2011. Intra-uterine fetal death (IUFD) at or after 28 weeks of gestation was diagnosed on ultrasound. Complete obstetrical history including last menstrual period and history of loss of fetal movements was taken. In GPE blood pressure was recorded and other relevant examination were performed. In vaginal examination any bleeding was noted and umbilical cord was examined and cord prolapse recorded if present. Full blood count, fasting blood glucose level, urine sample collected in 24 hours and all other relevant investigations were performed. Results: Mean age of the patients was 37.00±2.46 years. 62 (40%) patients were primigravida and 93 (60%) were multigravida. Placental abruption was found in 52%, anemia in 8%, pre-eclampsia in 30%, eclampsia in 54%, diabetes mellitus in 18% and cord prolapse in 58% of the patients. Conclusion: Placental abruption, eclampsia, and prolapsed cord were found to be important factors in IUFD.